2015
DOI: 10.1002/chem.201501546
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Diastereomeric Interconversions of β‐Sulfinylsubporphyrins as Evidence for Bowl Inversion

Abstract: B-Methoxy β-(4-methoxyphenylsulfinyl)subporphyrin and B-phenyl β-(4-methoxyphenylsulfinyl)subporphyrin were synthesized by oxidation of the corresponding β-sulfanylsubporphyrins with m-chloroperbenzoic acid and were separated into diastereomers, respectively. B-Methoxy subporphyrin diastereomers were interconverted to each other in methanol or ethanol, whereas such interconversion was not observed for B-phenyl subporphyrin diastereomers even at high temperature. Diastereomeric interconversions of B-methoxy sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…A facile racemization of 5 in solution was also seen in the CD measurements, which revealed that the CD signals of a freshly isolated sample gradually decreased at 40 °C in chloroform (Figure S6). Because 6Fr1 and 6Fr2 with an axial phenyl ligand were not racemized under similar conditions, the racemization of 5 may proceed through a bowlto-bowl inversion mechanism via a planar subporphyrin cation formed in a SN1-type heterolysis of the axial B-OH bond in solution at elevated temperatures (Scheme 2) [21]. Although similar SN1-type heterolysis of 4 can occur in solution, thermal racemization was not observed for 4Fr1 and 4Fr2 at a similar temperature range as tested for racemization of 5.…”
Section: Resultsmentioning
confidence: 99%
“…A facile racemization of 5 in solution was also seen in the CD measurements, which revealed that the CD signals of a freshly isolated sample gradually decreased at 40 °C in chloroform (Figure S6). Because 6Fr1 and 6Fr2 with an axial phenyl ligand were not racemized under similar conditions, the racemization of 5 may proceed through a bowlto-bowl inversion mechanism via a planar subporphyrin cation formed in a SN1-type heterolysis of the axial B-OH bond in solution at elevated temperatures (Scheme 2) [21]. Although similar SN1-type heterolysis of 4 can occur in solution, thermal racemization was not observed for 4Fr1 and 4Fr2 at a similar temperature range as tested for racemization of 5.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of 141 with m ‐CPBA delivered the respective sulfoxide in 35 % and 21 % (for the two diastereomers), and when the axial boron substituent was changed from OMe to Ph the yields increased to 52 % and 39 %. [ 202 ] The conversion to the sulfoxide enables the separation and isolation of the two diastereomers of the subporphyrin. These two diastereomers exhibited different 1 H NMR spectra, immediately noticeable through the ‐OC H 3 signal and the adjacent aryl protons.…”
Section: Snar Reactions Of Subporphyrinsmentioning
confidence: 99%
“…Because the bowl-to-bowl inversion was considered to hamper self-assembly of naphthalimide-annulated corannulene derivatives, we investigated this process by temperature-dependent 1 H-NMR spectroscopy in deuterated 1,1,2,2-tetrachloroethane (TCE-d 2 ). [17] Molecule 3 a is, however, not suitable for this kind of investigation due to the fast rotation of the phenyl rings attached to the imide units on the NMR time scale, making its protons indistuinguishable. In contrast, due to the two different faces (convex, concave) of the corannulene derivative and the steric hindrance of the diisopropylphenyl groups in molecule 3 b, the isopropyl groups attached at the phenyl ring in ortho position and the protons in meta position have different chemical environments and can therefore be distuinguished at room temperature ( Figure S5).…”
Section: Self-assembly Behaviormentioning
confidence: 99%
“…Usually, the activation barrier in sumanene systems is higher and subphthalocyanines usually do not undergo bowl inversion at all due to very high barriers. [17] Conformationally stable systems, in which the bowl-to-bowl inversion is hindered, can be aligned in the presence of an electric field to form one-dimensional columnar liquid crystalline materials due to their axial dipole moment, which is of interest for device applications. [18] Upon chemical reduction of corannulene and sumanene, highly negatively charged bowl-shaped ligands are obtained, forming a variety of intriguing sandwich-like complexes with different alkali metal cations on both the convex and the concave surface of the ligand, which have been characterized in their crystalline state and by NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%